2020
DOI: 10.3892/mco.2020.2095
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of baseline neutrophil‑to‑lymphocyte ratio in metastatic solid tumors

Abstract: High baseline neutrophil-to-lymphocyte ratio (NLR) has been associated with poor survival in a number of solid tumors, but has not been extensively investigated in the context of radiation oncology. Developing more robust models to predict survival would inform patient care for patients with metastatic solid tumors. The present study was undertaken to evaluate the effect of baseline NLR (using 4 as a cutoff) on survival in 320 consecutive patients with metastatic cancer who were referred to a single radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The observations that neutrophils frequently accumulate in peripheral blood and resected metastatic cancer tissues of advanced cancer patients [ 9 , 10 ] suggest a possible association between neutrophils and metastasis. Extensive studies have confirmed the causal link between elevated neutrophil counts and increased risk for metastasis as well as poor prognosis [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The observations that neutrophils frequently accumulate in peripheral blood and resected metastatic cancer tissues of advanced cancer patients [ 9 , 10 ] suggest a possible association between neutrophils and metastasis. Extensive studies have confirmed the causal link between elevated neutrophil counts and increased risk for metastasis as well as poor prognosis [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this feature can be used as an indicator of systemic inflammation, but it is recognized as a poor prognostic factor in various cancers, including BC. 4 Furthermore, it is currently accepted that an aberrant innate and/or adaptive immune response contributes to tumorigenesis selecting aggressive clones by inducing immunosuppression as well as stimulating cancer cell proliferation and metastasis. 3 As far as breast tissue is concerned, specific immune cells are resident in the breast tissue and contribute to the homeostasis of the mammary gland.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are polymorphonuclear phagocytes that circulate peripheral blood and function as innate immunity against microbial pathogens. In patients with cancer, especially at advanced stages and after metastasis, the number of circulating neutrophils increases and high neutrophil-to-lymphocyte ratio (NLR) is associated with aggressive outcome [101][102][103]. Similarly, in tumor-bearing mice, the number of neutrophils also increases in peripheral blood and is also associated with aggressive outcome and metastatic potential [104,105].…”
Section: Cancer-related Circulating Neutrophilsmentioning
confidence: 99%